Pengaruh Kualitas Produk, Gaya Hidup Dan Brand Image Terhadap Keputusan Pembelian Iphone Di Kota Mataram - Yopan Hidayat (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2025)
The purpose of this study is to determine (1) the Effect of Product Quality on I Phone Purchasing Decisions in Mataram City (2) The Influence of Lifestyle on I Phone Purchasing Decisions in Mataram City (3) The Influence of Brand Image on I Phone Purchase Decisions in Mataram City. The type of research used in this study is descriptive analysis research. The type of data used in this study is quantitative data. The population in this study is consumers of iPhone smartphone users in the Mataram city area, which is as many as 272 people. The analytical tool used in this study is SPSS 16. The results showed that (1) product quality did not have a partial effect on purchasing decisions. This is evidenced by the results of the T test where the product quality variable has a calculated value of < ttable (1.511 < 1.96). (2) There is a partial influence of lifestyle on purchasing decisions. This is evidenced by the results of the T test where the lifestyle variable has a calculated value of > ttable (7.726 > 1.96). (3) There is a partial influence of brand image on purchasing decisions. This is evidenced by the results of the T test where the brand image variable has a calculated value of > ttable (3.346 > 1.96). (4) Product quality, lifestyle and brand image simultaneously influence purchasing decisions. This is evidenced by the results of the F-count has a value of 7.607 greater than the F-table which is 2.683.